Financing surface transportation in the United States forging a sustainable future now! : summary of the Fourth International Conference - Perez, Benjamin G. (Conference proceedings (National Research Council (U.S.). Transportation Research Board) ;, 2012)
"TRB's Conference Proceedings 48: Financing Surface Transportation in the United States: Forging a Sustainable Future--Now summarizes a May, 2010 conference that focused on developments in innovative funding techniques and options for securing continued revenue to support national infrastructure and mobility needs. Views presented in Conference Proceedings 48 reflect the opinions of the individual participants and are not necessarily the views of all conference participants, the planning committee, TRB, or the National Research Council."--Pub. desc.